Descending towards the light: A comparative analysis of the de-(con)structive poetics Ada Salas and Eduardo Scala - Carrasco Gil, Celia (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This essay proposes an approach to the works of Ada Salas and Eduardo Scala from the analysis of their logophagic figures. Starting from elements such as the negation of the tópos, silence, the sonorous dimension, water as a common symbol and the archaeology and subsequent architecture of the word, this essay presents a comparative thematic approach to both works. The essay is based on the logophagic theory thar Túa Blesa stated in 1998 as an open catalogue in constant movement, capable, therefore, of adapting to different textual realities. In these pages I try to answer to the new theoretical needs posed by the elocutio of Salas and Scala. From an analysis that pays attention to their de-(con)structive poetics, this work focuses on the thematic constants with structuring potential of the lyric genre and, therefore, of both fragmentary discourses.